Building a Natural and Cultural Heritage Repository for the Storage and Dissemination of Knowledge: The Algarium Veneticum and the Archivio di Studi Adriatici Case Study. Issue 2 (3rd April 2017) - Minicante, Simona Armeli; Birello, Giancarlo; Sigovini, Marco; Minuzzo, Tiziano; Perin, Anna; Ceregato, Alessandro
ABSTRACT: The Archivio di Studi Adriatici (ASA) is a repository of the Institute of Marine Sciences (ISMAR-CNR) of Venice. The ASA repository, completely open source and open access, hosts natural collections, heritage books, documents, and maps of the Institute of Marine Sciences. It was developed following the discovery of a historical algal collection at the Biblioteca Storica di Studi Adriatici of Venice. This collection, after having been catalogued, has been digitized with a digital planetary scanner. Digitized specimens and metadata, compiled using Dublin Core and Simple Darwin Core formats, are hosted on a website, based on Fedora Repository and Islandora framework.